The Implementation of Science Process Skill (SPS)-based Matriculation to Equalize Scientific Literacy of Prospective Elementary Teacher - Hanifah Mulyani; Rizki Hadiwijaya Zulkarnaen; Nenden Permas Hikmatunisa; Iik Iklimah; Tiar Mutiarani (Postgraduate, University of Mataram, 2026)
Elementary teachers play a crucial role in fostering students’ scientific literacy; however, many prospective teachers still demonstrate only moderate levels. This study aimed to provide a comprehensive overview of Science Process Skills (SPS)-based matriculation program designed to enhance their scientific literacy. A mixed-method approach with a convergent parallel design was employed, in which quantitative and qualitative data were collected concurrently, analyzed separately, and subsequently integrated. The participants consisted of 24 first-semester of PGSD students, selected through purposive sampling. The results of the Wilcoxon test revealed a significant difference between pretest and posttest scores (p < 0.001), with an average increase of 16.9 points following the program. Further analysis using N-gain and t-test (t(23) = -10.3, p < 0.001) confirmed the effectiveness of the matriculation was indicated as a low-to-moderate level. Thematic analysis indicated that the program supported students in reconstructing their understanding, as well as increasing their interest and confidence in learning science. Nevertheless, several challenges were identified, particularly related to time constraints and the organization of physics concept delivery. In conclusion, the SPS-based matriculation program was effective in enhancing the scientific literacy of prospective elementary teachers with further refinement is required to optimize its outcomes.